The Nyikok Tradition of Lampung Pepadun Indigenous People as a Fulfillment of Children's Rights and its Relevance to Indonesian Islamic Family Law - Saputra, Aldila Leo (SMART: Journal of Sharia, Traditon, and Modernity, 2023)
This research examines the implications of the nyikok tradition in Lampung Pepadun customary society on the fulfillment of children's rights and its relevance to the development of Islamic family law in Indonesia. This type of research is field research, which is conducted in the Lampung Pepadun indigenous community in Lampung Province. This type of research is field research, which is conducted in the Lampung Pepadun Customary Society in Lampung Province. Data sources in this research are primary and secondary data sources. Data analysis in this research uses qualitative methods. Analyzed inductive thinking approach. The results of the study that Nyikok in Lampung Pepadun cultural customs has a good purpose. Based on the Receptio A Contrario analysis, nyikok has compatibility with Islamic law, so that its practice can be applied by the indigenous people of Lampung Pepadun, because it has positive implications in fulfilling children's rights, on the other hand, it is also to protect the inherited property of the deceased father, to continue the breed so that the balance is not broken and to maintain the kinship system that has been established. The nyikok tradition has relevance to Islamic family law in Indonesia, which is relevant to KHI Article 14, Article 2 (1) of Law No. 1 of 1974 concerning Marriage and then the existence of nyikok in the context of child protection and care is relevant to Article 45 of Law No. 1 of 1974 concerning Marriage, that parents have an obligation to maintain and educate children.Keyword: Nyikok; Lampung Pepadun; Children's Rights; Indonesian Family Law.